Bewegungsresistente Verben - Fortmann Christian (Zeitschrift für Sprachwissenschaft, 2007)
In German, three types of morphologically complex verbs have to be distinguished with respect to V2-movement. Complex verbs either move as a whole or leave behind a particle or do not move at all. I argue that the latter type – ursenden (first broadcast), ehebrechen (commit adultery) – and a subclass of the first type – wetteifern (rival) – are derived from complex nominalisations – Ursendung (first broadcast), Ehebruch (adultary), Wetteifer (rivalry) – by affixation of a (mostly unpronounced) verbalizing suffix. Diverging from a frequent view, I do not assume that immobility is due to an ambiguous word structure. While verbs like wetteifern are V0-categories, hence, accessible to V2-movement, immobile verbs like ehebrechen are projections which result from raising of the first element of the nominal compound and its adjunction to the derived verb. As projections are excluded from V2-movement, these verbs cannot move as a whole. But they do not allow for movement leaving behind a particle, either. This fact is attributed to conditions on interpretation of the resulting chains that would be offended in this case. This view is also motivated by the fact that immobile verbs are interpreted compositionally. The prefixed element functions as an argument or an adverbial modifier of the verb because it ccommands the verbalizing suffix. Moveable denominal verbs, instead, have a non-compositional, idiomatic reading since the first element of the nominal does not c-command the verbalizing suffix.